Большая книга ужасов. Коллекция кошмаров: [повести] / художник Н. Никонова - Никонова Наталья (Большая книга ужасов, 2015)
Экземпляры: ф.4 (20151012) / Инвентарный номер: 059450 / Цена: 257.00 / Авт.знак: Б 79 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6